Mengidentifikasi Kesehatan Mental Siswa Melayu yang Terlibat Histeria dengan Menggunakan Tes Drawing A Person - Nagarubini Paramasivam (Duconomics Sci-meet (Education & Economics Science Meet), 2022)
Malaysians frequently use the term hysteria to describe an illness caused by a subtle disturbance or ghost disturbance. The DSM-5 classifies Conversion disorder or hysteria under ‘somatic symptom and related disorders’ with conversion disorder being bracketed as ‘functional neurological symptom disorder’. This trust derives from Malays' belief that the anger is unsettling delicate and otherworldly beings. The main purpose of this study is to establish a hysteria profiling among Malay students using clinical psychology approach. A qualitative approach, psychological tests and triangulation method were used for this study, in which 10 specific hysteria students was selected for in Drawing A person test. The psychological test was Drawing Test. Snow ball sampling was used to select young girls in high schools who experienced mass hysteria. The findings show that secondary school girls in Kelantan experience both physical and psychological symptoms during mass hysteria episodes and that it has a contagious effect. The profile of hysteria students can be concluded as they were influenced by different types personality, higher level of depression, stress and anxiety. The mass hysteria in the Kelantan context is better understood, teachers can be empowered through health education to enable them to identify mass hysteria outbreaks in schools early, manage victims and observers more effectively and refer victims to health workers for treatment.